Anticorrosion: Oil‐Impregnated Nanoporous Oxide Layer for Corrosion Protection with Self‐Healing (Adv. Funct. Mater. 15/2017). (13th April 2017) - Lee, Junghoon; Shin, Sangwoo; Jiang, Youhua; Jeong, Chanyoung; Stone, Howard A.; Choi, Chang‐Hwan
Abstract : In article number 1606040, Chang‐Hwan Choi and co‐workers develop a solvent exchange method that allows the full impregnation of oil into nanopores of anodized aluminum. The nanoporous oxide layer with fully and stably entrained oil shows significantly enhanced corrosion resistance and water‐repellency with great durability and self‐healing, which is of great significance in many applications such as naval systems.